2020
DOI: 10.1177/1120672119899901
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in diabetes: A review

Abstract: Diabetic retinopathy is a common diabetes complication representing a heavy burden in terms of visual impairment and heath expenditure. Optical coherence tomography angiography is a relatively new imaging method and has proven to be a powerful tool in the analysis of diabetic retinopathy common features, including microaneurysms, intraretinal microvascular abnormalities, or neovascularization, as well as in research field, challenging the gold standard of fluorescein angiography. Many studies underlined the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…Recent technical advances in ocular imaging techniques, most importantly the introduction of optical coherence tomography angiography (OCT-A), allow for the non-invasive visualization and quantification of retinal microvascular changes [ 36 ]. OCT-A provides depth-resolved images of the retinal and choroidal vasculature approaching almost histological resolution, which has considerably increased our understanding of microvascular alterations in patients with diabetes [ 37 ]. Furthermore, OCT-A allows for the quantification of vascular density in different layers of the retinal vascular tissue and might, therefore, be a suitable tool to monitor disease progression.…”
Section: Microvascular Changes In Patients With Diabetesmentioning
confidence: 99%
“…Recent technical advances in ocular imaging techniques, most importantly the introduction of optical coherence tomography angiography (OCT-A), allow for the non-invasive visualization and quantification of retinal microvascular changes [ 36 ]. OCT-A provides depth-resolved images of the retinal and choroidal vasculature approaching almost histological resolution, which has considerably increased our understanding of microvascular alterations in patients with diabetes [ 37 ]. Furthermore, OCT-A allows for the quantification of vascular density in different layers of the retinal vascular tissue and might, therefore, be a suitable tool to monitor disease progression.…”
Section: Microvascular Changes In Patients With Diabetesmentioning
confidence: 99%
“…OCTA analysis was also revealed to be useful in characterizing retinal alterations in diabetic eyes [18][19][20][21]. Overall, these studies demonstrated early retinal perfusion changes in these eyes.…”
Section: Introductionmentioning
confidence: 71%
“…Several studies have used 2D OCTA to demonstrate that retinal perfusion is affected in diabetic eyes [18][19][20][21]. In patients affected by type 2 diabetes and DR, 2D perfusion and vessel length densities-that are based on the area of thresholded vessels and on a map with vessels of 1-pixel width, respectively-were proved to be reduced in eyes with non-proliferative DR.…”
Section: Discussionmentioning
confidence: 99%
“…26 Capillary vascular density and visual acuity reduce in proportion to disease severity in systemic diseases involving impairments to the blood-retinal barrier and retinal blood flow, such as diabetes. 27,28…”
Section: Discussionmentioning
confidence: 99%